2010
DOI: 10.1111/j.1600-0447.2010.01659.x
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant ventral striatal responses during incentive processing in unmedicated patients with obsessive-compulsive disorder

Abstract: These findings provide neural evidence for altered incentive processing in unmedicated patients with OCD, suggesting an elevated sensitivity to negatively affect stimuli as well as dysfunction of the ventral striatum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 48 publications
6
47
1
1
Order By: Relevance
“…Using a monetary incentive-delay task, Jung et al . [515] found increased frontostriatal activation during monetary-reward outcome, and decreased lateral prefrontal and inferior parietal cortex activation during loss anticipation, but no group differences during monetary-reward anticipation. However, Figee and colleagues [516] did find relatively decreased NAc activity during reward anticipation in OCD, particularly in those patients with contamination fear.…”
Section: Reviewmentioning
confidence: 99%
“…Using a monetary incentive-delay task, Jung et al . [515] found increased frontostriatal activation during monetary-reward outcome, and decreased lateral prefrontal and inferior parietal cortex activation during loss anticipation, but no group differences during monetary-reward anticipation. However, Figee and colleagues [516] did find relatively decreased NAc activity during reward anticipation in OCD, particularly in those patients with contamination fear.…”
Section: Reviewmentioning
confidence: 99%
“…Despite strong arguments for a role of altered processing of negative and ambiguous feedback in the pathophysiology of OCD, no neuroimaging studies haveto the best of our knowledgeinvestigated the processing of ambiguous feedback in OCD. Furthermore, no imaging studies have explored the processing of feedback valence in OCD outside the context of monetary incentives (Remijnse et al, 2006;Figee et al, 2011;Jung et al, 2011) with the latter studies yielding only partially consistent results. Remijnse et al (Remijnse et al, 2006) explored brain activation of OCD patients during a reversal task with monetary reward and loss feedback and showed attenuated activation of orbitofrontal cortex (OFC) and caudate nucleus in OCD patients to reward feedback.…”
Section: Introductionmentioning
confidence: 97%
“…During loss feedback, however, no differential brain activation was observed. More recent studies reported diminished activation of the nucleus accumbens during reward anticipation and of medial frontal cortex during reward delivery in patients (Figee et al, 2011), and higher insular activation during loss anticipation relative to neutral anticipation (Jung et al, 2011). None of these studies reported activation of the cingulate cortices, which are typically involved in error and conflict processing in OCD (Saxena et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Способность принимать решения оценивалась с помощью карточного Айова-теста (Iowa gambling test) и отсроченного задания с денежным стимулом (Monetary incentive delayed task). Снижение показателей указанных тестов у пациентов с ОКР было связано с активацией ле-вой префронтальной коры и левого хвостатого ядра по данным нейровизуализации [33,34].…”
Section: о б з о р ы о с н о в н ы е х а р а к т е р и с т и к и л о unclassified